Research-informed teacher education, teacher autonomy and teacher agency: the example of Finland (UCL Press, 2023)
Finnish education has received worldwide attention due to the country's performances in the Programme for International Student Assessment (PISA). Research investigating Finland's positive outcomes in the assessment has highlighted not only the strength of teachers, but also the rigour of Finnish teacher education. Finnish student teachers must undertake research-based teacher education culminating in a master's degree. The study of educational science, underpinned by empirical research, creates teacher-researchers. A Nordic/Continental view of educational governance allows for input control in terms of a national core curriculum in Finland, without surveillance of outcomes. The structure of the Finnish education system, characterised by decentralisation and the national core curriculum, entrusts teachers to make their own pedagogical decisions. This leads to autonomous and agentic teachers in terms of decision-making on the classroom, school, and professional levels, both individually and collectively. Finnish education, underpinned by social democratic values, views education as an agent of social change. Therefore, teachers enact social transformation through the agency enabled by research-informed teacher education. Finland's political consensus regarding education and societal trust in teachers further reinforces teacher autonomy and agency. This article argues that the rigorous research focus of Finnish teacher education cultivates autonomous and agentic teachers.